Principles of Profit Taxation of Commercial Banks in Russia and Abroad - Konvisarova, Elena V.; Stihiljas, Ilona V.; Koren, Andrey V.; Kuzmicheva, Irina A.; Danilovskih, Tatjana E. (International Journal of Economics and Financial Issues, 2016)
Commercial banks, due to their position in the financial system, are a necessary part in ensuring the correct and timely tax payments to the state budget, which certainly affects the economy as a whole. Despite of the periodical changes in legal bank taxation, in regulation and in reforming, the banks are not still the “locomotive” of the economy. Therefore, the study of foreign practice of taxation and its analysis will allow us not to repeat the mistakes and to use the experience to expedite the process of civilized market reforms in Russia. The article deals with the taxation of profits of commercial Banks in Russia and in developed countries of the world. The comparative analysis of profit taxation practice in Russia, USA, UK, Germany and France is made. The characteristic, applied to financial and credit institutions types of taxes and tax rates, is done. Tax incentives and suggested ways of improvement of taxation in commercial Banks in the Russian Federation and foreign countries are analyzed. The most effective ways of tax impact of the state on banking activities are considered, their detailed characteristics is given. On the basis of the conducted research, the conclusions about the relatively low tax load of banks in the Russian Federation and the high differentiation of tax rates in the United States were made. However, the main ways of tax policy improvement in the banking sector are related to the efficiency of interaction between government and financial-credit organizations. Keywords: taxes, commercial banks, the taxation of banks abroad, tax banking, , tax on banks' income, tax breaks JEL Classifications: H23, G21, C58, F30